Efektivitas Penggunaan Inaportnet Dalam Pelayanan Kapal Di PT. Pelayaran Nasional Indonesia (PELNI) Cabang Makassar - Muhammad Azhar Shauqy; Steven Rendy Kojansouw; Arif Fuddin Usman; Mutmainnah Mutmainnah; Yusri Yusri (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The Inaportnet system is an internet-based single service information system with the aim of integrating standard port information systems in ship services from all relevant agencies or stakeholders in the port environment. The purpose of this portal development is to accelerate port clearance. The research was conducted at PT. The Indonesian National Shipping (PELNI) Makassar Branch for 1 month from November 2021 to December 2021. The source of the data obtained is qualitative data, namely the data presented in the form of related information and the quality of the object under study. Results Based on the research, the use of the Inaportnet system at PT. Pelayaran Nasional Indonesia (PELNI) Makassar Branch Inaportnet system The process of submitting a ship service application using the Inaportnet system is very easy to use, and the Inaportnet system also encourages the submission of ship service applications. Constraints and alternative solutions in using the Inaportnet Maintenance system, to overcome this problem the submission of ship services is changed to a manual system so that the service submission process continues. HR, to overcome this problem, you must carefully check the ship's documents before the ship arrives at the port. Comparison before and before the application of the Inaportnet system in submitting ship services, before the application of the Inaportnet system agents still visited the relevant agencies (manual system), after the implementation of the Inaportnet system all made the system online.